English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

The problem is 3x(squared) +6x +3 = 0

The choices for the answer are:

x=1
x=-1
x=0
no real solution

2006-11-25 08:27:17 · 4 answers · asked by tia 3 in Science & Mathematics Mathematics

4 answers

Factor out 3.
3(x^2+2x+1)=0
3(x+1)^2=0
The only answer then is x=-1 to make the expression equal 0.

2006-11-25 08:30:45 · answer #1 · answered by KateG 2 · 0 0

Mrs? Trying to look smart for the kid? Ok, the way I learned to do this is by completing the square... 3x^2 + 6x + 3 = 0 x^2 + 2x + 1 = 0 (divide out the common factor) (x + 1)^2 = 0 (well, there's no need to complete the square here since (x+a)=x^2+2ax+a^2 by inspection) x+1 = 0 (taking square roots on both sides) x = -1 (subtract 1 from both sides) voila, you deduct 1 point from the boy for making you resort to yahoo! answers to do his homework.

2016-05-23 02:07:30 · answer #2 · answered by Anonymous · 0 0

3x2 + 6x +3 =0
(3x + 3) (x+1) = 0
x= -1 x= -1

therefore in this equation the only solution is (-1)

2006-11-25 08:36:57 · answer #3 · answered by Questioner 2 · 0 0

x= -1
use (-B+/-square root(B2-4AC))/2A

2006-11-25 08:37:11 · answer #4 · answered by Zack C 3 · 0 0

fedest.com, questions and answers